The Locked Doors a novel - McFadden, Freida (Naperville, IL Poisoned Pen Press, 2021)
While eleven-year old Nora Davis was up in her bedroom doing homework she had no idea her father was killing women in the basement. Until the day the police arrived at their front door. Decades later, Nora's father is spending his life behind bars and Nora is a successful surgeon with a quiet, solitary existence. Nobody knows about her past and she'll do anything to keep it that way. Then one of her young female patients is murdered, killed in the same horrific manner that her father used to kill his victims. Somebody knows who Nora is. Somebody wants her to take the fall for this unthinkable crime. But she's not like her father. The police can't pin anything on her. As long as they don't look is her basemet...
Keywords: Murder -- Fiction; Father -- Fiction; Narcissist -- Fiction; Psychopath -- Fiction; Suspense fiction; Psychological fiction; Thrillers (Fiction)